Smart and secure data storage using Encrypt-interleaving - Jeyaprabha, T. J.; Sumathi, G.; Nivedha, P. (2017 Innovations in Power and Advanced Computing Technologies (i-PACT), 2017)
In the recent years many companies are shifting towards cloud for expanding their business profit with least additional cost. Cloud computing is a growing technology which has emerged from the development of grid computing, virtualization and utility computing. Cloud computing is a model for enabling convenient, on-demand network access to a shared pool of configurable computing resources like networks, servers, storage, applications, and services that can be rapidly provisioned and released with minimal management effort or service provider interaction. There was a huge data loss during the recent Chennai floods during Dec 2015. If these data would have been stored at distributed data centers great loss could have been prevented. Though, such natural calamities are tempting many users to shift towards the cloud storage, security threats are inhibiting them to shift towards the cloud. Many solutions have been addressed for these security issues but they do not give guaranteed security. By guaranteed security we mean confidentiality, integrity and availability. Some of the existing techniques for providing security are Cryptographic Protocols, Data Sanitization, Predicate Logic, Access Control Mechanism, Honeypots, Sandboxing, Erasure Coding, RAID(Redundant Arrays of Independent Disks), Homomorphic Encryption and Split-Key Encryption. All these techniques either cannot work alone or adds computational and time complexity. An alternate scheme of combining encryption and channel coding schemes at one-go is proposed for increasing the levels of security. Hybrid encryption scheme is proposed to be used in the interleaver block of Turbo coder for avoiding burst error. Hybrid encryption avoids sharing of secret key via the unsecured channel. This provides both security and reliability by reducing error propagation effect with small additional cost and computational overhead. Time complexity can be reduced when encryption and encoding are done as a single process.